Design of Force Sensor with Large Range for Load Control of Cranes - Vu, Van Quang; Vu, Toan Thang (Old Journal, 2019)
Researches of designing and producing force measurement systems are receiving considerable attention of scientists and research groups over the world. Such systems are built under various principles and applied into different industrial fields. In this research, the authors are focused on designing a simple load cell by using force tensors in order to control the load of cranes. The measurement range of the sensor is up to 10000 N, with the nonlinearity under 2%. The paper also provides analysis and calculation of important parameters, thus, it is allows to manifest various sensors with similar designs but with different measured ranges.